Factors affecting managerial accounting of production and business costs in coal mining enterprises in Vietnam - Ms. Pham Thi Thu Hoai (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study was conducted with the aim of finding solutions to improve the efficiency of production and business cost management accounting activities in a number of coal mining enterprises in Vietnam. This study uses two main research methodologies, “exploratory factor analysis” and “multivariate regression” to solve the research objectives. A number of new findings have been researched as a solid basis for solutions to enhance the effectiveness of management accounting activities on production and business costs in the coal enterprises mentioned above.